The Emerging Role of Complement Lectin Pathway in Trypanosomatids: Molecular Bases in Activation, Genetic Deficiencies, Susceptibility to Infection, and Complement System-Based Therapeutics. (21st February 2013) - Evans-Osses, Ingrid; de Messias-Reason, Iara; Ramirez, Marcel I.
Abstract : The innate immune system is evolutionary and ancient and is the pivotal line of the host defense system to protect against invading pathogens and abnormal self-derived components. Cellular and molecular components are involved in recognition and effector mechanisms for a successful innate immune response. The complement lectin pathway (CLP) was discovered in 1990. These new components at the complement world are very efficient. Mannan-binding lectin (MBL) and ficolin not only recognize many molecular patterns of pathogens rapidly to activate complement but also display several strategies to evade innate immunity. Many studies have shown a relation between the deficit of complement factors and susceptibility to infection. The recently discovered CLP was shown to be important in host defense against protozoan microbes. Although the recognition of pathogen-associated molecular patterns by MBL and Ficolins reveal efficient complement activations, an increase in deficiency of complement factors and diversity of parasite strategies of immune evasion demonstrate the unsuccessful effort to control the infection. In the present paper, we will discuss basic aspects of complement activation, the structure of the lectin pathway components, genetic deficiency of complement factors, and new therapeutic opportunities to target the complement system to control infection.